Sentinel Node Biopsy and Lumpectomy in a Patient with Machado–Joseph Disease - N. N. Aldawoodi; A. R. Escher Jr.; A. Padalia; D. Padalia (Case Reports in Anesthesiology, 2019)
Spinocerebellar ataxia 3 (SCA3), also known as Machado–Joseph disease (MJD) is an autosomal dominant, progressive neurodegenerative disorder. Patients present with cerebellar ataxia, dystonia, rigidity, and neuropathy that worsen with time. On a molecular level, it occurs due to a CAG trinucleotide repeat expansion in the ATXN3 gene. Due to the risk of pulmonary aspiration, hypoventilation, autonomic and thermoregulatory dysfunction, vocal cord paralysis, progressive paraplegia, parkinsonian symptoms, and chronic pain, it has significant anesthesia implications. Rarely, case reports occur in the literature describing regional anesthetic management of patients with SCA3, but none that describe general anesthesia specifically with MJD. We therefore describe a case of a patient with SCA3 who successfully underwent general anesthesia and considerations for perioperative management of this patient population.